Perlindungan Hukum Terhadap Keselamatan dan Kesehatan Tenaga Kesehatan Akibat Pandemi Covid 19 - Santy Febryaningsih (Pusat Riset dan Inovasi Nasional, 2022)
Health workers are noble jobs and professions that are at the forefront in dealing with health problems, especially in the midst of the COVID-19 pandemic crisis. Health workers have to sacrifice their lives to protect the community from the spread of the covid-19 pandemic, health workers are also worried about the covid-19 pandemic, especially many health workers who are exposed to Covid-19 and the death of health workers, especially doctors and nurses. The implementation of safety and health for health workers aims to provide protection for health workers to be healthy, safe, productive, and avoid work accidents and occupational diseases. This research is focused on positive legal policies in Indonesia that regulate legal protection for the right to work safety for health workers who deal with the COVID-19 outbreak. The legal research used is normative legal research, the results of the study show that legal protection and fulfillment of the right to work safety for health workers who deal with the covid-19 pandemic outbreak are regulated in Indonesian laws.